2020
DOI: 10.3390/e22070714
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Encoding in Stochastic Latent-Variable Models

Abstract: In this work we explore encoding strategies learned by statistical models of sensory coding in noisy spiking networks. Early stages of sensory communication in neural systems can be viewed as encoding channels in the information-theoretic sense. However, neural populations face constraints not commonly considered in communications theory. Using restricted Boltzmann machines as a model of sensory encoding, we find that networks with sufficient capacity learn to balance precision and noise-robustness in order to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Presumably, neurons in the brain use a local heuristic that can be computed based on information available to single synapses. It was recently shown that local activity statistics indeed correlate with importance as assessed by FI (Rule et al, 2020). In the case of the RBM this correspondence is exact; an entry of the FIM for an RBM has the form (Rule et al, 2020):…”
Section: An Activity-dependent Estimate Of Fisher Informationmentioning
confidence: 94%
See 4 more Smart Citations
“…Presumably, neurons in the brain use a local heuristic that can be computed based on information available to single synapses. It was recently shown that local activity statistics indeed correlate with importance as assessed by FI (Rule et al, 2020). In the case of the RBM this correspondence is exact; an entry of the FIM for an RBM has the form (Rule et al, 2020):…”
Section: An Activity-dependent Estimate Of Fisher Informationmentioning
confidence: 94%
“…Through sampling we can average over ,ℎ . For instance, for two weights and connecting a presynaptic to a postsynaptic neuron, respectively, we get (Rule et al, 2020):…”
Section: An Activity-dependent Estimate Of Fisher Informationmentioning
confidence: 99%
See 3 more Smart Citations